Urban analysis as a strategy for the identification of routes and groups with heritage value in the city of San José, Costa Rica - Malavassi-Aguilar, Rosa Elena (2020)
This research aims to develop a strategy for understanding urban and architectural heritage in the city of San José, Costa Rica. With the application of urban analysis, which takes as a reference the proposals of the Italian architects Gianfranco Caniggia and Gian Luigi Maffei, are identified routes and groups with heritage value that include historical aspects and the imaginary of the citizens. The motivation for the development of this proposal is the search for a figure of alternative protection to the Historic Center, so that heritage conservation is achieved from a comprehensive approach. The primary sources for the development of this analysis are the maps and plans found in the National Archive of Costa Rica, which cover the period 1841-1982, and the aerial photographs of the city of San José from the period 1945-1998 provided by the National Geographic Institute. With these documents, is constructed a cartography with the use of a geographic information system. This work is located in the line of analysis of urban planning and architecture developed by Latin American authors such as Marina Waisman, in which  is proposed the development of own tools for the study of local heritage, so that the characteristics of the context are understood. The development of a tool such as the one proposed would be useful for the entities in charge of the protection of heritage and for the municipalities in their task of managing the regulatory plans, in which the protection zones must be included.